Immunogenicity and safety of yellow fever vaccine in HIV-1-infected patients. (23rd October 2018) - Colin de Verdiere, Nathalie; Durier, Christine; Samri, Assia; Meiffredy, Vincent; Launay, Odile; Matheron, Sophie; Mercier-Delarue, Séverine; Even, Sophie; Aboulker, Jean-Pierre; Molina, Jean-Michel; Autran, Brigitte; Simon, François
Abstract : Objectives: The objective of this study is to investigate immunogenicity and safety of the yellow fever vaccine (YFV) in HIV-infected (HIV+) patients with high CD4 + T-cell counts. Design: In this prospective, comparative study of YFV-naive adults: 40 HIV+ under antiretroviral therapy (ART) with CD4 + T-cell count above 350 cells/μl and plasma HIV-RNA less than 50 copies/ml for at least 6 months and 31 HIV-negative (HIV−) received one injection of the YF-17D strain vaccine. Methods: Serologic response was assessed by using a plaque reduction neutralizing test and YFV-specific T cells by using an INFγ-Elispot assay. Results: YFV was well tolerated in both groups. Most participants had asymptomatic YFV viremia at day (D) 7 after vaccination (77% of HIV− and 82% of HIV+, P = 0.58), with higher plasma level of YFV RNA in HIV+ than in HIV− (median 2.46 log10 copies/ml (range: 1.15–4.16) and 1.91 log10 copies/ml (1.15–3.19), respectively, P = 0.011). A significant but transient decrease in CD4 + cell counts was seen at D7 in both groups, more pronounced in HIV− than in HIV+ patients (−261.5 versus −111.5 cells/μl, respectively, P = 0.0003), but no HIV breakthrough was observed in plasma. All participants developed protective neutralizing antibody levels from D28 and up to 1 year after injection. At D91, fewer HIV+ than HIV− participants exhibited YFV T-cell response (20 versus 54%, respectively, P = 0.037). Conclusion: At 1 year, YFV was immunogenic and well tolerated in HIV-infected adults under ART with CD4 + T-cell counts above 350 cells/μl. However, a lower immunity of YFV T cells in HIV-infected patients was observed as compared with HIV− participants. Clinical Trials Registration: NCT01426243. Abstract : Supplemental Digital Content is available in the text